Opening the black box on bank efficiency in Bangladesh - Sufian, Fadzlan; Kamarudin, Fakarudin (Universiti Putra Malaysia Press, 2014)
The paper examines internal (bank specific) and external (macro and market) determinants of profit efficiency in the Bangladesh banking sector. The analysis consists of two stages. In the first stage, Data Envelopment Analysis (DEA) method was employed to compute profit efficiency of 31 commercial banks operating in the Bangladesh banking sector during the period of 2004 to 2011. In the second stage, panel regression analysis was used to examine contextual factors influencing the productive efficiency of banks. It was found that credit risk, non-interest income and bank size negatively influenced bank profit efficiency. On the other hand, the findings indicate that lower (higher) liquidity has positive (negative) impacts on the profit efficiency of banks operating in the Bangladesh banking sector. Nonetheless, no statistically significant influence of ownership structures was found on bank profit efficiency. Likewise, Bangladesh banks seemed not to have been significantly affected by the global financial crisis. The paper could be extended to include more variables, the non-parametric Malmquist Productivity Index (MPI) method and production function, along with intermediation function. The findings from this study are expected to contribute significantly to regulators, bank managers, investors, and also the existing knowledge on the level of profit efficiency of the Bangladesh banking sector. The paper seeks to provide for the first time empirical evidence on the profit efficiency of the Bangladesh banking sector.